Appearance of extrachromosomal circular DNAs during in vivo and in vitro ageing of mammalian cells - Kunisada, Takahiro; Yamagishi, Hideo; Ogita, Zen-ichi; Kirakawa, Tadashi; Mitsui, Youji (Mechanisms of ageing and development, 1985)
Appearance of extrachromosomal circular DNAs with in vivo and in vitro cellular ageing was examined by using a new technique of mica-press-adsorption for electron microscopy. The size distribution and the copy number of circular DNA complexes varied, depending on the cellular age. Extrachromosomal circular DNA complexes of variable length of more than 0.5 μm or 1.5 kilobase (kb) appeared during in vivo ageing of rat lymphocytes and in vitro ageing of cultured human lung fibroblasts. A restricted size class of circular forms of less than 0.5 μm in contour length was amplified in human skin fibroblasts from aged normal or Werner's syndrome subjects. These circular DNA molecules are suggested to be products of DNA rearrangements or gene amplification occurring in the chromosome.